Single-Shot Common-Path Off-Axis Dual-Wavelength Digital Holographic Microscopy Based on Two-Dimensional Grating Diffraction - Wang, Jieyu; Wang, Xue; Dong, Zhao; Wang, Huaying; Zhu, Qiaofen; Men, Gaofu; Gao, Yafei; Wang, Wenjian (Frontiers in Physics, 2022)
We present a single-shot dual-wavelength common-path off-axis digital holographic microscopic (CO-DHM) imaging method based on two-dimensional grating diffraction. This method improves the utilization rate of the interference field under the limited photosensitive size of the camera, and further expands the original camera's field of view (FOV). In addition, the mode of orthogonal carrier frequencies close to the diagonal direction can optimize the utilization of the camera's spatial bandwidth. Compared with the traditional dual-wavelength CO-DHM using one-dimensional grating or prism beam splitting, this method effectively avoids the aliasing of high-frequency components of the +1-order spectrum of different wavelengths in the frequency domain. We provide quantitative phase imaging experiments for the full FOV of USAF resolution chart, onion epidermal cells and standard polystyrene beads. The results prove that the system can enlarge the interferometric FOV by nearly 74.0% without changing the imaging parameters, such as magnification and resolution, and can achieve high-precision quantitative phase imaging with only a single hologram.